PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DI BURSA EFEK INDONESIA STUDI PADA SEKTOR CONSUMER GOODS PERIODE 2015-2019 - Noviarti; Xva Habillah (Jurnal Manajemen, 2020)
The purpose of this research is to find out if there is an effect of of Managerial Ownership, Institutional Ownership, Board Of Commissioners of Company Value of the sector Consumer Goods that listed at Indonesia Stock Exchange (IDX) for period 2015-2019. Population in this research is all sector Consumer Goods companies that listed in Indonesia stock Exchange (IDX) in the year 2015-2019. The sample in this research is 40 companies with porposive sampling as the sampling technique. Methods if data analysis in this research using linier regression analysis. The results of this research show that Managerial Ownership, Institutional Ownership, Board Of Commissioners partial has no effect on Company Value. The results also showed simultaneously that Managerial Ownership, Institutional Ownership, Board Of Commissioners effect on Company Value.